An economic approach to sports injury policies - Cisyk, J.; Courty, P. (Journal of Sports Economics, 2024)
We propose an analysis of sports injury policies founded on the assertion that injuries are due to both uncontrollable risks (accidents from participating in sports) and controllable risks (athlete's deliberate choices in risk-taking). We compare the adoption decision of an injury policy made by: (a) a sport's organizer who maximizes welfare, (b) a sport's organizer who fails to account for athletes` behavioral risk responses, and (c) the athletes themselves. We argue that policies that escalate risk, such as mandatory protective equipment, are over-adopted by the naïve sport organizer and the athletes, while policies that de-escalate risk, such as return-to-play rules, are under-adopted.